2007
DOI: 10.2519/jospt.2007.2296
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric Training Decreases Paratendon Capillary Blood Flow and Preserves Paratendon Oxygen Saturation in Chronic Achilles Tendinopathy

Abstract: a chilles tendinopathy is associated with a certain degree of neovascularisation 15 and pain, which may be demonstrated by either color Doppler or Power Doppler ultrasound. The introduction of Laser Doppler supports imaging in soft tissue inflammation and is believed to be more sensitive than Power Doppler. 5The baseline Achilles tendon as well as paratendon microcirculation in healthy athletes differs from patients with either insertional or midportion tendinopathy, where capillary blood flow at the point of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 21 publications
1
66
0
8
Order By: Relevance
“…It has been reported that nerves appear to travel in close association to tendon neovessels [5]. This finding suggests that angiogenesis plays an important role in pain-experienced in tendinopathy condition [6,7]. These data are in accordance with clinical studies showing that strategies to destroy neovessels (i.e local injection of a sclerosing agent, polidocanol) lead to pain improvement [7].…”
Section: Discussionsupporting
confidence: 80%
“…It has been reported that nerves appear to travel in close association to tendon neovessels [5]. This finding suggests that angiogenesis plays an important role in pain-experienced in tendinopathy condition [6,7]. These data are in accordance with clinical studies showing that strategies to destroy neovessels (i.e local injection of a sclerosing agent, polidocanol) lead to pain improvement [7].…”
Section: Discussionsupporting
confidence: 80%
“…There are 3 studies with level I evidence 108,110,120 and 11 studies with level II evidence. 5,25,31,56,75,77,97,111,114,117,121 Although these studies generally note good outcomes with athletic individuals who have midportion Achilles tendinopathy, it is reported that nonathletic individuals 75,114 and those with insertional Achilles tendinopathy 31 do not seem to respond as favorably. Curwin and Stanish 22 developed the eccentric program in the early 1980s.…”
Section: Eccentric Loadingmentioning
confidence: 94%
“…The eccentric program was found to be superior to low-energy shock wave treatment 110 ; however, extracorporeal shockwave therapy (ESWT) combined with the eccentric program was better than eccentric exercises alone. 108 Additional studies have also noted an eccentric training program for those with midportion Achilles tendinopathy to decrease pain, 5,31,56,77,111,117 improve function, 111 improve VISA-A scores, 25,75,120 and increase strength. 5 Concentric exercises do not seem to have the same effect as an eccentric program.…”
Section: Eccentric Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered that hypoxia could be responsible for neovascularization in tendinopathies, capillary flow and post-capillary pressure decreased following 12 weeks of eccentric loading [57].…”
Section: Discussionmentioning
confidence: 99%